THE INFLUENCE OF THE LEADER IN THE ORGANIZATIONAL CULTURE FORMATION - D. M. Safina (Russian Journal of Economics and Law)
The article considers different approaches to the classification of organizational cultures, a comparison of typologies of organizational cultures from the point of view of influence of the leader on the formation and maintenance of culture, analyzes the impact of leadership styles on organizational climate, and provides examples showing the actions of the leaders on the formation of organizational culture, describes the mechanisms of formation and maintenance of customer-oriented culture.